A produção de textos na escola : o aprendizado da escrita com base no desenvolvimento de sequências didáticas - Kusiak, Sandra Mara (2015)
This work is linked to the studies on the process of teaching of the Portuguese language focusing on the production of texts. Based on Geraldi (1999), Bronckart (2006), Dolz and Schneuwly (2004), Bakhtin (1997), beside others that guide the discussions about language and work with texts of genres in the classroom, a sequence was developed didactic in order to determine whether such pedagogical work organization modality produce impacts on the teaching activity and the practice of texts written by students. The study was developed by the researcher teacher with a group of students of the 6th year of primary education in a state school in a city in Rio Grande do Sul. The didactic sequence aimed at treating a genre texts rarely addressed in room class, the encyclopedia entry. For analysis, twelve texts are used, text production result of six students by means of which it is possible to collate the initial output and the final production of texts. Some episodes are recovered through autoscopy - video recordings produced and analyzed by the researcher and teacher of the class - and the recovery of the advances, limitations, expectations and transformations going through the practice of the researcher. The work represents a significant step in achieving a practice that combines studies on teaching Portuguese to the practice of planning and didactic implementation. This study also represents great social relevance, as it may support other teachers in their searches for alternatives to the problems that they face in the classroom and in their researches.